A European perspective on "clean eating": Commentary on Negowetti et al. (2021). Issue 1 (22nd September 2021) - Ghaderi, Ata
Abstract: Negowetti et al. (2021) have provided insightful perspectives on the public health implications of the labeling of "clean" dietary products in the United States through a scoping review, along with feasible strategies to counteract the risks of this trend. Although the European Union has already fairly strict regulations about declaration of ingredients and health claims regarding food that makes it almost impossible to label food products as "clean, " the clean eating trend is alive and expanding in Europe, and usage of expressions such as "clean" or "pure" in other ways than on the label may convey similar messages that cannot be regulated by law. Increased regulation, legislation, and information through the U.S. Food and Drug Administration as suggested by Negowetti et al. (2021) is a welcome contribution and will certainly help to prevent some misinformation. However, labels are just one battle field in addressing misleading expressions and trends. Scientists should enter the relevant fields (e.g., Internet, TV, and social media) to a higher extent and provide solid, pedagogical and simple facts, and guidelines to vaccinate people against current and upcoming misleading dietary trends.